Inter-state public-private partnership: aspects of financial convergence - Kulai, Alina; Кулай, Аліна Василівна (Vysoká škola finanční a správní, 2015)
In the article we examined the main models and forms of public-private partnership, their role in the socio-economic development and deepening of financial convergence of countries-participants of the partnership. The attention was paid to decentralization of inter-state forms of public-private partnership as the basis of cross-border and transnational partnership. The scientific research, described in this publication, have found their practical application in the realization of the project within Euro-region “Bug”. This project has founded a joined Ukrainian – Polish institution of labor migration administration and also of granting necessary permissions for realization activities within Ukraine.
Integrační modely a formy spolupráce veřejného a soukromého sektoru: aspekty finanční konvergence
Keywords: partnership; state and private partners; migration; cross-border and transnational cooperation; convergence; taxes; financial systems